Vision and depth perception tests for the visual aid (UI20190059) developed for monocular vision impaired patients - Ravindran N.; Mohamed H.; Ismail I.N.; Isa M.R. (American Institute of Physics Inc., 2024)
This paper evaluates the effectiveness of the visual aid design (UI20190059) intended to help monocular vision impaired patients. The primary objectives of this visual aid are to increase the field of vision and provide a depth perception for the user to help distinguish depth in their vision. Two types of tests were conducted on the visual aid with respondents, the field of vision test and the depth perception test. Based on the visual field measurement test, the visual aid has improved the respondents' visual field, ranging from 132 to 176 degrees. Furthermore, from the depth perception test, all respondents could identify the objects correctly with the help of the visual aid. Thus, the visual aid design was proven to offer the respondents visual improvement. The design, however, may need to undergo more clinical trials before actual patients can fully use it. 2023 AIP Publishing LLC.